Development of Future Learning Models Based on Ki Hajar Dewantara’s Ideas: A Bibliometric Evaluation of Recent Research - Ali, Ali Anhar Syi'bul Huda; Syahidin; Hermawan, Wawan (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2024)
This study investigates the application of Ki Hajar Dewantara's ideas in the development of future learning models through a bibliometric approach. By analyzing 500 publications from Google Scholar, Scopus, and Web of Science spanning the period 2014-2024, the study identifies key trends, highlights the contributions of leading researchers, and explores central themes in the related academic discourse. The findings reveal a significant increase in publications related to Dewantara's ideas, with a notable peak in 2023. Key topics identified include character education, independent curricula, and value-based learning. Additionally, the research underscores the global relevance of Dewantara's educational philosophy, aligning with the humanistic principles espoused by John Dewey and Paulo Freire. The implications for Indonesian education involve reinforcing the role of the Tri Center of Education and enhancing the integration of character values within the national curriculum. The study further recommends the development of technology-driven research and the adoption of hybrid learning models. Abstrak: Penelitian ini menyelidiki penerapan gagasan Ki Hajar Dewantara dalam pengembangan model pembelajaran masa depan melalui pendekatan bibliometrik. Dengan menganalisis 500 publikasi dari Google Scholar, Scopus, dan Web of Science yang mencakup periode 2014-2024, penelitian ini mengidentifikasi tren utama, menyoroti kontribusi peneliti terkemuka, dan mengeksplorasi tema-tema sentral dalam diskursus akademik terkait. Temuan menunjukkan adanya peningkatan signifikan dalam publikasi yang berkaitan dengan gagasan Dewantara, dengan puncak yang mencolok pada tahun 2023. Topik-topik utama yang teridentifikasi meliputi pendidikan karakter, kurikulum mandiri, dan pembelajaran berbasis nilai. Selain itu, penelitian ini menegaskan relevansi global dari filosofi pendidikan Dewantara, yang sejalan dengan prinsip humanistik yang diajarkan oleh John Dewey dan Paulo Freire. Implikasi untuk pendidikan Indonesia mencakup penguatan peran Tri Center of Education dan peningkatan integrasi nilai karakter dalam kurikulum nasional. Penelitian ini juga merekomendasikan pengembangan riset berbasis teknologi dan adopsi model pembelajaran hybrid.